Collocation approximations for weakly singular Volterra integro‐differential equations - I. Parts; A. Pedas (Mathematical Modelling and Analysis, 2003)
A piecewise polynomial collocation method for solving linear weakly singular integro‐differential equations of Volterra type is constructed. The attainable order of convergence of collocation approximations on arbitrary and quasi‐uniform grids is studied theoretically and numerically.